First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Reaction mechanisms of coal gasification in supercritical water with CO2 transport agent: A ReaxFF molecular dynamics study - Ruiqi Mu; Ming Liu; Jingqi Gao; Kai H. Luo; Junjie Yan (Fuel, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Polymeric membranes for sustainable closed-loop heamodialysis process water management: Recent advances and future perspectives - Nuhu Dalhat Mu'azu; Mukarram Zubair; Hissah A. Alqahtani; Shamsuddeen A. Haladu; Mohammad Saood Manzar; Salha Alharthi; Abir Abdel-Naby; Ahmad Hussaini Jagaba; Ishraq H. Alhamed; Emre Cevik; Abdullah Alhwiesh; Nadeem Baig (Journal of Environmental Chemical Engineering, 2025)

Effects of wilting duration and microbial inoculation on fermentation profile, chemical composition, aerobic stability and in situ nutrient degradability of ryegrass silage - F.X. Amaro; K.G. Arriola; L. Mu; S. Farooq; C. NinoDeGuzman; C. Romeiro; L.O. Lima; H. Sultana; A.O. Oyebade; M. Wallau; D. Vyas (Animal Feed Science and Technology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Understanding and recent advances on lithium structural batteries - Zhongjiu Yang; Yuhe Mu; Luiz H. Acauan; Jen-Hung Fang; Marianna Rogers; Muhammad K. Majeed; Jin Luo; Yue Zhou (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Advancements and prospects in the utilization of metal ions and polymers for enhancing aerobic granulation during industrial effluent treatment and resource recovery - Ahmad Hussaini Jagaba; Dahiru U. Lawal; Ismail Abdulazeez; Ibrahim Mohammed Lawal; Nuhu Dalhat Mu'azu; Abdullahi Haruna Birniwa; Abdullahi Kilaco Usman; Haithm Salah Hagar; Nura Shehu Aliyu Yaro; Azmatullah Noor; Kunmi Joshua Abioye; Jun Wei Lim; et al. (Journal of Water Process Engineering, 2024)

Nickel augmented biochar for sustaining produced water treatment to decarbonize oil and gas industrial waste using anaerobic-aerobic granular cylindrical periodic discontinuous batch reactors - Ahmad Hussaini Jagaba; Dahiru U. Lawal; Mohamed A. Yassin; Ismail Abdulazeez; Nuhu Dalhat Mu'azu; Abdullahi Kilaco Usman; Jun Wei Lim; Isam H. Aljundi (Environmental Research, 2024)

A review on the application of biochar as an innovative and sustainable biocarrier material in moving bed biofilm reactors for dye removal from environmental matrices - Ahmad Hussaini Jagaba; Ismail Abdulazeez; Dahiru U. Lawal; Augustine Chioma Affam; Nuhu Dalhat Mu’azu; Usman Bala Soja; Abdullahi Kilaco Usman; Azmatullah Noor; Jun Wei Lim; Isam H. Aljundi (Environmental Geochemistry and Health, 2024)

Methanogenic biodegradation of thermoplastic poly(vinyl alcohol) films produced by two manufacturing processes in enrichment cultures - Ming-Le Ji; Yi-Fan Liu; Yu Bai; Zhen Hu; James H. Wang; Jia-Yi Li; Wan-Qi Qin; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Yingcheng Li; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

Inland waterway traffic noise prediction model: a comparison - B. L. Dai; N. Sheng; J. Huang; F. H. Mu; X. Chen; T. Li; J. M. Xu; Y. L. He (International Journal of Environmental Science and Technology, 2024)

Indoor air pollution exposure and early childhood development in the Upstate KIDS Study - Alexandra Grippo; Kexin Zhu; Edwina H. Yeung; Erin M. Bell; Matthew R. Bonner; Lili Tian; Pauline Mendola; Lina Mu (Environmental Research, 2023)

Efficient denitrification by a salt-tolerant aerobic compound bacteria agent AHM M3: optimizing composition and reduction conditions - H. Ma; Y. Liu; X. Mu; J. Song; X. Su; Y. Wu; R. Han (International Journal of Environmental Science and Technology, 2023)

Photoperiod drives cessation of wood formation in northern conifers - Wenhuan Mu; Xiuchen Wu; J. Julio Camarero; Yongshuo H. Fu; Jianguo Huang; Xiaoyan Li; Deliang Chen (Global Ecology and Biogeography, 2023)
Aims Shifts in xylem phenology directly determine the forest capacity for carbon sequestration. However, a systematic understanding of the spatial patterns and the underpinning drivers in determining the cessation of wood formation ( C cw ) is lacking at a pan‐continental scale. Here, we addressed this knowledge gap by compiling a new dataset of multiple xylem phenology timings for northern conifers. Locations Sixty‐two study sites, Northern Hemisphere (25–55° N). Time period 2003–2018 (16 years). Taxa Thirty‐three conifer species. Methods A generalized additive model was fitted to characterize the latitudinal pattern in C cw . Structural equation modelling and a linear mixed‐effects model were applied to determine the main drivers underlying the latitudinal pattern in C cw . Results The C cw followed a flat S‐shaped pattern with increasing latitude. Photoperiod was the dominant determinant of the latitudinal pattern of C cw , and a longer photoperiod was associated with an earlier C cw . Both mean growing‐season temperature and total growing‐season precipitation exhibited significantly positive relationships to the cessation of cell elongation and thus the C cw across all study sites. In arid regions, the pre‐growing‐season temperature had a significantly negative effect on C cw . In humid regions, C cw was positively affected by the mean growing‐season temperature. The onset of wood formation showed significantly positive coupling with C cw at arid sites but not at humid sites. Early successional species were sensitive to hydrothermal variations during the pre‐growing season. Main conclusions We reveal the dominant role of photoperiod in determining the cessation of wood formation for northern conifers and highlight differentiated interactive effects between photoperiod and seasonal climatic factors and the preceding xylem phenophases in determining C cw among ecoregions and tree species. These insights provide evidence to reduce uncertainty in prediction of the forest carbon uptake potential and the consequent biophysical feedbacks of northern forests.

Biophysical Reviews special issue call: quantitative methods to decipher cellular heterogeneity — from single-cell to spatial omic methods - Joshua W. K. Ho; Xi Chen; Mu He; Yuanhua Huang; Jessica C. Mar; David J. H. Shih; Angela R. Wu (Biophysical Reviews, 2022)

Productivity of Leymus chinensis grassland is co-limited by water and nitrogen and resilient to climate change - Yujie Shi; Yunna Ao; Baixin Sun; Johannes M. H. Knops; Jinwei Zhang; Zhihan Guo; Xianming De; Jiayu Han; Yuheng Yang; Xiaoyu Jiang; Chunsheng Mu; Junfeng Wang (Plant and Soil, 2022)

Salt intake and gastric cancer: a pooled analysis within the Stomach cancer Pooling (StoP) Project - Samantha Morais; Adriana Costa; Gabriela Albuquerque; Natália Araújo; Claudio Pelucchi; Charles S. Rabkin; Linda M. Liao; Rashmi Sinha; Zuo-Feng Zhang; Jinfu Hu; Kenneth C. Johnson; Domenico Palli; et al. (Cancer Causes & Control, 2022)

Fibroblast Growth Factor 9 Stimulates Neuronal Length Through NF-kB Signaling in Striatal Cell Huntington’s Disease Models - Issa Olakunle Yusuf; Hsiu-Mei Chen; Pei-Hsun Cheng; Chih-Yi Chang; Shaw-Jenq Tsai; Jih-Ing Chuang; Chia-Ching Wu; Bu-Miin Huang; H. Sunny Sun; Chuan-Mu Chen; Shang-Hsun Yang (Molecular Neurobiology, 2021)

Synthesis of a Novel Composite Sorbent Coated with Siderite Nanoparticles and its Application for Remediation of Water Contaminated with Congo Red Dye - Musa Alshammari; Maad F. Al Juboury; Laith A. Naji; Ayad A. H. Faisal; Hongshan Zhu; Nadhir Al-Ansari; Mu Naushad (International Journal of Environmental Research, 2020)
Re-use of the byproduct wastes resulting from different municipal and industrial activities in the reclamation of contaminated water is real application for green projects and sustainability concepts. In this direction, the synthesis of composite sorbent from the mixing of waterworks and sewage sludge coated with new nanoparticles named “siderite” (WSSS) is the novelty of this study. These particles can be precipitated from the iron(II) nitrate using waterworks sludge as alkaline agent and source of carbonate. Characterization tests using X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) mapping revealed that the coating process was correctly achieved and siderite nanoparticles were planted on the surface of the composite sorbent. Interaction between Congo Red dye and composite sorbent was evaluated through a set of batch tests under the variation of agitation time, pH of aqueous solution, and sorbent dosage. The results proved that the prepared sorbent had a high ability in the treatment of water contaminated with Congo Red dye in comparison with previous studies and the maximum adsorption capacity reached to maximum value i.e. 9416 mg/g. The sorption process was governed by electrostatic attractions; however, Sips and Pseudo-second-order models described this process with coefficient of determination greater than 0.99. Graphic abstract

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

WormBot, an open-source robotics platform for survival and behavior analysis in C. elegans - Jason N. Pitt; Nolan L. Strait; Elena M. Vayndorf; Benjamin W. Blue; Christina H. Tran; Brendon E. M. Davis; Karen Huang; Brock J. Johnson; Keong Mu Lim; Sophie Liu; Arash Nikjoo; Anuj Vaid; et al. (GeroScience, 2019)

Development of an inland waterway traffic noise prediction model considering water surface adsorption and embankment shielding influences - B. L. Dai; N. Sheng; Y. L. He; F. H. Mu; J. M. Xu; A. F. Zhu (International Journal of Environmental Science and Technology, 2019)

Trade-offs and synergies between seed yield, forage yield, and N-related disservices for a semi-arid perennial grassland under different nitrogen fertilization strategies - Yujie Shi; Junfeng Wang; Xavier Le Roux; Chunsheng Mu; Yunna Ao; Song Gao; Jinwei Zhang; Johannes M. H. Knops (Biology and Fertility of Soils, 2019)

Fish invasion in the river systems of Guangdong Province, South China: Possible indicators of their success - D. E. Gu; Y. C. Hu; M. Xu; H. Wei; D. Luo; Y. X. Yang; F. D. Yu; X. D. Mu (Fisheries Management and Ecology, 2018)
Although a large number of fish species have been introduced into Guangdong Province in Southern China, a few species, such as tilapia ( Tilapia spp.), North African catfish Clarias gariepinus Burchell, mrigal carp, Cirrhinus mrigala (Bloch) and the sucker mouth catfish ( Hypostomus sp.), have established natural populations and can be considered “successful invaders” in large rivers. The specific mechanisms underlying these contrasting results among different introduced fish species remain understudied. The relationship between multiple abiotic–biotic factors and the success of four invasive species was investigated using survey data for the Guangdong Province river ecosystem. In contrast to previous studies that have considered species‐specific traits, the focus was on economic, ecological and anthropogenic factors to predict invasion success. Four main predictive indicators were found: (1) successful invaders were of low or no commercial value; (2) successful invaders tolerated a wide range of environmental conditions, including poor water quality; (3) biodiversity loss accelerated the growth of non‐native populations; (4) human disturbance facilitated population growth and spread of invasive fish species. To lessen the impacts of invasive fish species, the selection of breeding species and breeding areas, maintenance of water quality and reduction in water pollution, protection of the diversity of fish species and reduction of human interference should be addressed.

RHEB1 insufficiency in aged male mice is associated with stress-induced seizures - Qi Tian; Pavel Gromov; Joachim H. Clement; Yingming Wang; Marc Riemann; Falk Weih; Xiao-Xin Sun; Mu-Shui Dai; Lev M. Fedorov (GeroScience, 2017)

Increased productivity in wet years drives a decline in ecosystem stability with nitrogen additions in arid grasslands - Junfeng Wang; Johannes M. H. Knops; Chad E. Brassil; Chunsheng Mu (Ecology, 2017)
Adding nutrients to nutrient‐limited ecosystems typically lowers plant diversity and decreases species asynchrony. Both, in turn, decrease the stability of productivity in the response to negative climate fluctuations such as droughts. However, most classic studies examining stability have been done in relatively wet grasslands dominated by perennial grasses. We examined how nutrient additions influence the stability of productivity to rainfall variability in an arid grassland with a mix of perennial and annual species. Of the nutrients, only nitrogen increased productivity, and only in wet years. In addition, only nitrogen decreased the stability of productivity. Thus, nutrient addition makes ecosystem productivity less stable in both wet and arid grasslands. However, the mechanism is very different. In contrast to wet grasslands, adding nitrogen to an arid grassland did not decrease diversity. Rather, stability decreased with nitrogen addition due to an increase in annual species that increased productivity. In other words, in our arid grassland, nitrogen addition decreased ecosystem stability because of increased ecosystem responsiveness to positive climate fluctuations. These climate fluctuations were facilitated by annual species that take advantage of wet years and can escape dry years as seeds. Our data support the conclusion that nutrient additions decrease the stability of productivity in both wet and arid grasslands. Nutrient enrichment increases the sensitivity of productivity to low rainfall years in wet grasslands, whereas nutrient enrichment in arid grasslands increases the sensitivity of productivity to high rainfall years.

Grain boundary wetness of partially molten dunite - Shangshang Mu; Ulrich H. Faul (Contributions to Mineralogy and Petrology, 2016)

Clinical characteristics of 154 patients suspected of having Ebola virus disease in the Ebola holding center of Jui Government Hospital in Sierra Leone during the 2014 Ebola outbreak - T. Yan; J. Mu; E. Qin; Y. Wang; L. Liu; D. Wu; H. Jia; Z. Li; T. Guo; X. Wang; Y. Qin; Y. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

A novel microbead-based microfluidic device for rapid bacterial identification and antibiotic susceptibility testing - J. He; X. Mu; Z. Guo; H. Hao; C. Zhang; Z. Zhao; Q. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Apoptosis repressor with caspase recruitment domain is regulated by MAPK/PI3K and confers drug resistance and survival advantage to AML - P. Y. Mak; D. H. Mak; H. Mu; Y. Shi; P. Ruvolo; V. Ruvolo; R. Jacamo; J. K. Burks; W. Wei; X. Huang; S. M. Kornblau; M. Andreeff; et al. (Apoptosis, 2014)

Assessment of the MODIS global evapotranspiration algorithm using eddy covariance measurements and hydrological modelling in the Rio Grande basin - A. L. Ruhoff; A. R. Paz; L. E. O. C. Aragao; Q. Mu; Y. Malhi; W. Collischonn; H. R. Rocha; S. W. Running (Hydrological Sciences Journal, 2013)

Satellite‐derived estimates of forest leaf area index in southwest Western Australia are not tightly coupled to interannual variations in rainfall: implications for groundwater decline in a drying climate - Keith R. J. Smettem; Richard H. Waring; John N. Callow; Melissa Wilson; Qiaozhen Mu (Global Change Biology, 2013)
There is increasing concern that widespread forest decline could occur in regions of the world where droughts are predicted to increase in frequency and severity as a result of climate change. The average annual leaf area index ( LAI ) is an indicator of canopy cover and the difference between the annual maximum and minimum LAI is an indicator of annual leaf turnover. In this study, we analyzed satellite‐derived estimates of monthly LAI across forested coastal catchments of southwest Western Australia over a 12 year period (2000–2011) that included the driest year on record for the last 60 years. We observed that over the 12 year study period, the spatial pattern of average annual satellite‐derived LAI values was linearly related to mean annual rainfall. However, interannual changes to LAI in response to changes in annual rainfall were far less than expected from the long‐term LAI ‐rainfall trend. This buffered response was investigated using a physiological growth model and attributed to availability of deep soil moisture and/or groundwater storage. The maintenance of high LAI s may be linked to a long‐term decline in areal average underground water storage and diminished summer flows, with an emerging trend toward more ephemeral flow regimes.

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Expression profiles of seven channel catfish antimicrobial peptides in response to Edwardsiella ictaluri infection - J W Pridgeon; X Mu; P H Klesius (Journal of Fish Diseases, 2012)
Using quantitative polymerase chain reaction (QPCR), the relative transcriptional levels of seven channel catfish antimicrobial peptide (AMP) genes (NK‐lysin type 1, NK‐lysin type 2, NK‐lysin type 3, bactericidal permeability‐increasing protein, cathepsin D, hepcidin and liver‐expressed AMP 2) in response to Edwardsiella ictaluri infection were determined. None of the AMP genes tested was significantly upregulated at 2 h post‐infection. Hepcidin was the only one that was significantly ( P P E. ictaluri , all lethal doses were able to induce significant ( P In vitro growth studies revealed that the presence of synthetic hepcidin peptide at a concentration of 16 μ m or higher significantly inhibited the cell proliferation of E. ictaluri . Taken together, our results suggest that hepcidin might play an important role in the channel catfish defence against E. ictaluri infection.

Modulation of high impulsivity and attentional performance in rats by selective direct and indirect dopaminergic and noradrenergic receptor agonists - Anushka B. P. Fernando; Daina Economidou; David E. Theobald; Mu-Fa Zou; Amy H. Newman; Marcia Spoelder; Daniele Caprioli; Margarita Moreno; Lucia Hipόlito; Albert T. Aspinall; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2012)

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

The chromosomal localization, expression pattern and polymorphism analysis of porcine FSCN1 gene differently expressed from LongSAGE library - Zh. L. Tang; X. J. Zhang; Sh. L. Yang; Y. L. Mu; W. T. Cui; H. Ao; K. Li (Molecular Biology Reports, 2010)

Partial molecular characterization, expression pattern, polymorphism and association analysis of porcine SKP2 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Evaluation of Combined Toxicity of Phenols and Lead to Photobacterium phosphoreum and Quantitative Structure–Activity Relationships - L. M. Su; Y. H. Zhao; X. Yuan; C. F. Mu; N. Wang; J. C. Yan (Bulletin of Environmental Contamination and Toxicology, 2010)

Expression and SNP association analysis of porcine FBXL4 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. Li; K. M. Peng (Molecular Biology Reports, 2010)

Partial molecular cloning, characterization, and analysis of the subcellular localization and expression patterns of the porcine OTUB1 gene - T. L. Shan; Z. L. Tang; D. Z. Guo; S. L. Yang; Y. L. Mu; Y. H. Ma; W. J. Guan; K. Li (Molecular Biology Reports, 2009)

PM2.5 and Associated Polycyclic Aromatic Hydrocarbon and Mutagenicity Emissions from Motorcycles - Hsi-Hsien Yang; Shu-An Lee; Dennis P. H. Hsieh; Mu-Rong Chao; Che-Yu Tung (Bulletin of Environmental Contamination and Toxicology, 2008)

100 years of Sediment History of Heavy Metals in Daya Bay, China - J. Z. Du; H. D. Mu; H. Q. Song; S. P. Yan; Y. J. Gu; J. Zhang (Water, Air, & Soil Pollution, 2008)

Interconversion Pharmacokinetics of Simvastatin and its Hydroxy Acid in Dogs: Effects of Gemfibrozil - Thomayant Prueksaritanont; Yue Qiu; Lillian Mu; Kimberly Michel; Janice Brunner; Karen M. Richards; Jiunn H. Lin (Pharmaceutical Research, 2005)

Comparison of Particle Image Velocimetry and Laser Doppler Anemometry Measurements in Turbulent Fluid Flow - M. P. Wernet; A. Subramanian; H. Mu; J. R. Kadambi (Annals of Biomedical Engineering, 2000)